2015
DOI: 10.1007/s12199-015-0480-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prenatal education curriculum on mother’s prenatal examination utilization, delivery mode and recovery status: a cross-sectional survey in China

Abstract: Objectives To examine the participation, implementation, and effect of the prenatal education curriculum provided by hospitals in China, and to provide evidence for the improvement of prenatal education. Methods A cross-sectional survey was conducted in the hospitals in Hunan Province, China. Mothers aged 20-45 years who had given birth between 1 May 2011 and 1 May 2012 and not diagnosed with pregnancy-related complications were invited to participate in the study. A self-administered, structured questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
13
0
1
Order By: Relevance
“…Our results were consistent with the results obtained in a previous study [22]. Prenatal education not only increased the rates of prenatal examinations and promoted communication with doctors but also improved women's attitudes towards delivery [16]. In addition, prenatal education can help pregnant women accept and adapt to the role of mother [23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were consistent with the results obtained in a previous study [22]. Prenatal education not only increased the rates of prenatal examinations and promoted communication with doctors but also improved women's attitudes towards delivery [16]. In addition, prenatal education can help pregnant women accept and adapt to the role of mother [23].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, pregnant women who receive prenatal education have a greater sense of well-being and satisfaction in terms of overall quality of life and health than those who do not [15]. However, a study in a Chinese population found that the rate of participation in prenatal education was very low due to lack of time and su cient resources [16].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the findings of this study, the results of a study (2015) in China showed that participation in childbirth preparation classes did not affect the method of delivery. They do not mention specific reasons for this, but they found that an improvement in the health of both mother and baby requires participation in these classes, and they considered conducting interventions to increase participation in these classes a critical measure …”
Section: Discussionmentioning
confidence: 99%
“…Even, globally, the exclusive breastfeeding rate is just about 43% [11]. The possible reason may be because most of the efforts and activities directed at improving the breastfeeding rate and duration are targeted at pregnant women and post-partum period [12,13].…”
Section: Introductionmentioning
confidence: 99%